2019
DOI: 10.1021/acsami.9b10905
|View full text |Cite
|
Sign up to set email alerts
|

A Zn(ClO4)2 Electrolyte Enabling Long-Life Zinc Metal Electrodes for Rechargeable Aqueous Zinc Batteries

Abstract: The degradation or dendrite formation of zinc metal electrodes has shown to limit the cycle life of rechargeable aqueous zinc batteries, and a few anode protection methods are proposed. We herein demonstrate that, except for external protections, a simple design of an electrolyte can effectively promote stable and facile Zn stripping/plating from/on zinc electrodes. By using Zn­(ClO4)2 in the aqueous electrolyte, reversible Zn stripping/plating is achieved for over 3000 h at 1 mA cm–2 current density and 1 mA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 44 publications
1
84
0
Order By: Relevance
“…Regarded as a potential alternative to Li-based battery anode materials, the Zn metal anode offers a high volumetric capacity (5854 mAh cm À3 ), [1] relative abundance and widespread distribution in the earth's crust, [2,3] and a low plating/stripping potential that can be accommodated in aqueous electrolytes. [4][5][6][7] However, poor cycling efficiency and dendrite formation stemming from parasitic reactions between the Zn metal and the electrolyte currently impede the practical deployment of a rechargeable Zn metal battery (RZMB). [8,9] This impediment has spurred significant research effort toward electrolyte development for RZMBs.…”
Section: Introductionmentioning
confidence: 99%
“…Regarded as a potential alternative to Li-based battery anode materials, the Zn metal anode offers a high volumetric capacity (5854 mAh cm À3 ), [1] relative abundance and widespread distribution in the earth's crust, [2,3] and a low plating/stripping potential that can be accommodated in aqueous electrolytes. [4][5][6][7] However, poor cycling efficiency and dendrite formation stemming from parasitic reactions between the Zn metal and the electrolyte currently impede the practical deployment of a rechargeable Zn metal battery (RZMB). [8,9] This impediment has spurred significant research effort toward electrolyte development for RZMBs.…”
Section: Introductionmentioning
confidence: 99%
“…The electrolyte containing an anion with variable valence can form a protective layer via reduction during repeated cycling process, like the solid electrolyte interface in lithium metal batteries. Wang et al 99 found that electrolytes with ClO 4 − could considerably enlarge the cycle life of Zn anodes. By detecting the existence of characteristic peak of Cl − , the XPS result of a Zn anode after cycling suggested that an insoluble chloride layer was formed on the surface of Zn because of the reduction of ClO 4 − .…”
Section: Corrosion and Hermentioning
confidence: 99%
“…[65,271] Although the perchlorate electrolyte is traditionally not considered as an ideal electrolyte, [10] a recent study demonstrates significant improvement in the cycling stability of ZIB when Zn(ClO 4 ) 2 was used instead of other common electrolyte such as ZnSO 4 . [264] Further studies are required to understand the use of perchlorate electrolyte in the fabrication of ZIB for practical applications. Various engineering strategies employed to achieve high capacity and long lifespan by tuning the electrolyte concentration/composition is illustrated in Scheme 6.…”
Section: Electrolyte Engineering Strategiesmentioning
confidence: 99%